Local Wisdom in The Interpretation of Religious Tolerance Verses in Tafsir Al-Ibriz By KH. Bisri Mustafa - Aprilianti, Anisatul Fikriyah (Proceedings of Annual Conference for Muslim Scholars, 2024)
Tolerance is a prerequisite for building interfaith communication to create peace in Indonesia. This is because Indonesia is a plural country. The idea of tolerance is found in the interpretation of the Qur'an, including in the interpretation of al-Ibriz by KH. Bisri Mustafa. This research explores the context of local wisdom in the interpretation of tolerance verses in tafsir al-Ibriz. This research is a qualitative research with textual analysis of the tafsir. The focus of this research is on the interpretation of tolerance verses in tafsir al-Ibriz, especially on five things: believer-unbeliever interaction, no compulsion in religion, living together with people of different religions, the existence of the people of the book, and Islam as a mercy to the universe. The results of this study found that the context of local wisdom contained in tafsir al-Ibriz is found in the interpretation and analysis written in Javanese. Tafsir al-Ibriz is addressed to Muslims in general, especially Muslims in Indonesia, especially in Java. In the context of pluralism, the writing of this interpretation is also intended to ground the Qur'an to a plural society.